Contribution to the knowledge of Diastatotropis Lacordaire including two resurrected names (Coleoptera: Anthribidae) - Trýzna, Miloš (Zootaxa, 2024)
Diastatotropis striata Wolfrum, 1961 stat. rest. and Diastatotropis viridans (Fairmaire, 1897) stat. rest. are resurrected as valid names from synonymy with Diastatotropis crassicornis Waterhouse, 1882. Redescriptions, differential diagnosis, colour photographs of relevant types, a key to species and new data on the distributions are presented. Photographs of morphologically similar species are also provided.